The Labour Party and the Nursing Profession - MacDonald, James Ramsay, 1866-1937 (London : The Labour Party (London : Co-operative Print. Society Ltd.), 1927)
1927 1927 1920s 40 pages 20 A standard of working hours is difficult to apply as it depends so much on local conditions, especially in a country district where the distances to be covered are greater. Sometimes an epidemic will cause the nurses to be badly overworked, sometimes there will be very little doing. On the whole, however, the local associations live up fairly well to the standard of the Institute which is that: — "The nurse is not to be on duty more than eight hours daily, except under special circumstances. On Sundays she shall only attend cases requiring special or immediate attention. Night duty shall only be undertaken under special circumstances when due provision can be made for other cases under her care. She shall be entitled to a month's holiday during the year, and shall have, if possible, half a day off every week and a week-end occasionally." Special conditions that apply to a few localities are given below. LONDON. There are 173 Queen's nurses working in London. There are, of course, local associations not employing Queen's nurses, and certain parishes employing trained nurses that are not affiliated to any association. There are also nurses, attached to special denominations working chiefly amongst members of their own congregations, but sometimes attending other sick persons in the neighbourhood if sent for, such as the Catholic Nursing Institute and the Little Sisters of the Assumption. The most important London organisation providing nurses, apart from Q.V.J.I., is the Ranyard Mission, which employs 84 nurses. These two organisations have a working arrangement whereby they do not duplicate each other's territory. They differ fundamentally in organisation inasmuch as the Ranyard nurses are not attached to any local association and are paid directly by the Mission itself. Despite its religious connections, the Ranyard nurses care for the sick poor without regard to creed. They must have had three years' hospital training plus six months' district training. Three experienced superintendent sisters visit them regularly during their work in the district. The working day averages from seven to eight hours, and night work must not be undertaken except in cases of emergency. Each nurse is allowed a holiday of five weeks during the year, half-a-day off each week or two free days each month. When first placed in a district a nurse is paid £59 16s. a year. At the end of two years this is raised to £63 18s. ; at the end of three years this is raised to £65. An allowance of £85 16s. per year is made for board, laundry, and lodging. Uniform is provided free. During the first three weeks of probation no salary is paid, but board and lodging are free. After the first three weeks and until the six months training is completed, the nurse receives £1 a week; during this time she lives in the home. Every nurse accepted on the permanent staff is required to join the Pension Fund unless she has adequate provision for the future, the mission paying, roughly, two-thirds of the premiums. In London there is a Central Council for District Nursing, which is a co-ordinating body founded in 1915. It distributes grants to district nursing associations from funds it has received from private foundations, the British Red Cross, and the Ministry of Health. The total grants disbursed in 1921 126/TG/RES/X/1036A/14